1996
DOI: 10.1677/joe.0.1490019
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary lactotrope expresses transforming growth factor β (TGFβ) type II receptor mRNA and protein and contains 125I-TGFβ1 binding sites

Abstract: Transforming growth factor beta 1 (TGF beta 1) has recently been shown to be produced in the prolactin (PRL)-secreting lactotropes of the pituitary gland. TGF beta 1 inhibits lactotropic secretion and proliferation, and the production of TGF beta 1 in lactotropes is reduced during lactotropic growth following estrogen treatment in ovariectomized rats. In many estrogen-responsive tissues, TGF beta 1 has been shown to exert its effect by binding to TGF beta 1 type II receptors (T beta R II) at the cell surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…The pituitary gland is a site where TGF-␤ acts locally to control cell growth and function and exerts growth-inhibiting and differentiating influences as it does on many other tissues (Ramsdell, 1991;Sarkar et al, 1992). Within the pituitary gland, lactotropes of the anterior lobe of the pituitary and melanotropes of the intermediate pituitary gland have been shown to produce TGF-␤1 and TGF-␤3 (Sarkar et al, 1992(Sarkar et al, , 1998Burns and Sarkar, 1993;De et al, 1995;Pastorcic et al, 1995). However, TGF-␤1 and TGF-␤3 are thought to have contrasting and opposite actions on lactotropic proliferation in the pituitary, with TGF-␤1 inhibiting pituitary cell growth, whereas TGF-␤3 increases lactotropic cell growth (Hentges et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The pituitary gland is a site where TGF-␤ acts locally to control cell growth and function and exerts growth-inhibiting and differentiating influences as it does on many other tissues (Ramsdell, 1991;Sarkar et al, 1992). Within the pituitary gland, lactotropes of the anterior lobe of the pituitary and melanotropes of the intermediate pituitary gland have been shown to produce TGF-␤1 and TGF-␤3 (Sarkar et al, 1992(Sarkar et al, , 1998Burns and Sarkar, 1993;De et al, 1995;Pastorcic et al, 1995). However, TGF-␤1 and TGF-␤3 are thought to have contrasting and opposite actions on lactotropic proliferation in the pituitary, with TGF-␤1 inhibiting pituitary cell growth, whereas TGF-␤3 increases lactotropic cell growth (Hentges et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory response to TGF-β1 is reduced in anterior pituitary cell lines, including the prolactin-secreting PR1 cell line and the GH and prolactin-secreting GH3 cell line. Both of these cell lines show low levels of TGF-β1 and its type II receptor (TβR-II) mRNA [67]. Lactotropes exposed to estrogen express reduced levels of TβR-II and TGF-β1 [68,69].…”
Section: Cell Growth Balance By Tgf-β Isoformsmentioning
confidence: 99%
“…One explanation for TGF-β3's inability to be self-inhibitory is that the TGF-β receptors on lactotropes have a low affinity for TGF-β3 [76]. Another possibility is that estrogen suppresses TGF-β that prevents the effect of TGF-β on lactotropes [67]. It has been shown that TGF-β1 inhibits lactotropic cell proliferation and that this response is mediated largely via the TGF-β type II receptors [67].…”
Section: Role Of Tgf-β Receptors In Mediation Of Tgf-β Isoform Actionmentioning
confidence: 99%
See 2 more Smart Citations